Design for Manufacturing and Assembly (DFMA) for BBQ Grill Machine - Johari Abd Razak, Alif Qayyum; Mohd Amri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The research consists of the analysis of three models of barbeque grill (BBQ Grill) using the Design for Manufacturing and Assembly (DFMA) method has been purposed. DFMA is approach to reduce and minimize the time of assembly, cost, and component on the existing product. BBQ Grill has become a common product in our daily life especially for use that usually use the BBQ Grill for family gathering. This product’s pricing in the marketplace does not offer consumers an opportunity to acquire it since the price is not reasonable for customers who use it for a brief time. The key for this research is to come up with a barbeque grill (BBQ Grill) which has superlative design efficiency and reduced cost of manufacturing by comparing three barbeque grill BBQ Grill which is Portable Charcoal Grill for Outdoor 18inch (Product 1), Char-Griller Classic Cart Style (Product 2) and Charcoal Kettle Grill with Cart BBQ (Product 3). Manual assembly is determined by remodeling the existing model in SolidWorks 2018 software for all three models. Product 1 which has 18.90% design efficiency compare to Product 2 and Product 3 were 9.87% and 15.54% design efficiency respectively. For the chosen design, Model 1 shows the risen of design efficiency after being a purpose of its new improved design namely Product 1-V2 from 18.90% to 19.64% which increased by 0.74%. There has been 5 modification made to Product 1-V2. The total reduction part is reduced by 4 parts from 47 parts on the original design to 43 parts on the newly improved design. Results from total absorption cost shows that the Product 1 is estimated at RM883.39 for 32 manufactured parts while the Product 1-V2 model costs around RM822.63 for 29 manufactured parts. There were RM 60.76 cost reductions between these two models.